Bacillus velezensis SYL-3 suppresses Alternaria alternata and tobacco mosaic virus infecting Nicotiana tabacum by regulating the phyllosphere microbial community - Liu, He; Jiang, Jun; An, Mengnan; Li, Bin; Xie, Yunbo; Xu, Chuantao; Jiang, Lianqiang; Yan, Fangfang; Wang, Zhiping; Wu, Yuanhua (Frontiers in Microbiology, 2022)
The occurrence of plant diseases is closely associated with the imbalance of plant tissue microecological environment. Regulation of the phyllosphere microbial communities has become a new and alternative approach to the biological control of foliar diseases. In this study, Bacillus velezensis SYL-3 isolated from Luzhou exhibited an effective inhibitory effect against Alternaria alternata and tobacco mosaic virus (TMV). Analysis of phyllosphere microbiome by PacBio sequencing indicated that SYL-3 treatment significantly altered fungal and bacterial communities on the leaves of Nicotiana tabacum plants and reduced the disease index caused by A. alternata and TMV. Specifically, the abundance of Pseudomonas, Sphingomonas, Massilia, and Cladosporium in the SYL-3 treatment group increased by 19.00%, 9.49%, 3.34%, and 12.29%, respectively, while the abundances of Pantoea, Enterobacter, Sampaiozyma, and Rachicladosporium were reduced. Moreover, the abundance of beneficial bacteria, such as Pseudomonas and Sphingomonas were negatively correlated with the disease indexes of A. alternata and TMV. The PICRUSt data also predicted the composition of functional genes, with significant differences being apparent between SYL-3 and the control treatment group. Further function analysis of the microbiome also showed that SYL-3 may induce the host disease resistance by motivating the host defense-related pathways. These results collectively indicate that SYL-3 may suppress disease progression caused by A. alternata or TMV through improving the microbial community composition on tobacco leaves.